Evaluating the Efficacy of Lysozyme Against Lactic Acid Bacteria Under Different Winemaking Scenarios - Azzolini, M.; Tosi, E.; Veneri, G.; Zapparoli, G. (South African Journal of Enology and Viticulture, 2016)
This study evaluated the efficacy of lysozyme in winemaking to control lactic acid bacteria (LAB). In a winery vinification, indigenous LAB were partially and completely inhibited when lysozyme was added to red and white grape must respectively. This result was confirmed by using two selected strains of Lactobacillus brevis and Oenococcus oeni to contaminate the grape must. In the red wine microvinification, the cell population decreased only temporarily and malolactic fermentation terminated at different times, depending on the grape must pH and lysozyme dosage. In the white wine microvinification, cell mortality rates differed according to lysozyme dosage rather than pH values. During the fermentation, lysozyme activity was stable or decreased, depending on the absence or presence of grape must respectively. The study highlighted that lysozyme efficacy is strongly affected by the type of vinification.